ОБГРУНТУВАННЯ МОЖЛИВОСТІ ПЕРЕДАЧІ СИГНАЛІВ ЦИФРОВОГО ТЕЛЕБАЧЕННЯ СТАНДАРТУ DVB-T2 ПО РАДІОРЕЛЕЙНІЙ ЛІНІЇ З ЧАСТОТНОЮ МОДУЛЯЦІЄЮ - Адамович, Олег Михайлович; Авдєєнко, Гліб Леонідович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Justification of transmissibility of digital television signals of the standard DVB-T2 via the frequency shift radio relay line Provision of state security and needs of the public with modern kinds and services of television broadcast is one of the most important goals of State television and radio broadcasting committee of Ukraine. The only effective way of creating such conditions is applying of already existed broadcast networks (e.g radio relay links) of TV programs and their further improving. On the basis of above-mentioned in order to broadcast the DVB-T2 TV signal, it is necessary to plan the applying of already existed facilities.